Immobilization of pectinase on reusable polymer support for clarification of apple juice - Rajdeo, Kishor; Harini, Tirunagari; Lavanya, Kuna; Fadnavis, Nitin W. (Food and Bioproducts Processing, 2016)
Pectinase (E.C.3.2.1.15) was successfully immobilized on recyclable polymer matrix. The immobilization matrix was prepared by reaction of polyethyleneimine (mol. wt. 70,000) with epoxy-activated acrylate copolymer DILBEAD-VWR. The enzyme pectinase was first adsorbed on the polymer at pH 7.0 via ion exchange and then stabilized by crosslinking with dextran aldehyde. While the free enzyme shows a pH-optimum of 5.0, the immobilized enzyme exhibited high level of activity in a broad pH range of pH 3.0-7.0. Although the thermal stability of free and immobilized enzymes was similar, at room temperature, the immobilized enzyme could be recycled more than 10 times with loss of less than 5% of its activity during clarification of apple juice. On the eventual loss of enzyme activity, the immobilized enzyme and dextran aldehyde can be easily removed from the polymer by a simple treatment with 1N HCl and the polymer can be reused for immobilization of a fresh batch of enzyme. This support also can be reused several times, making the process economically attractive. The properties of apple juice treated with immobilized enzyme were similar to those of that treated with free pectinase. (C) 2016 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Apple juice; Dextran aldehyde; Immobilization; Pectinase; Polyethyleneimine; Polymer